Improving reproductive outcomes in frozen embryo transfer over fresh embryo transfer in women with endometrioma: A historical cohort study - Parisa Pirooznia; Mehri Mashayekhi; Firouzeh Ghaffari; Nadia Jahangiri; Zahra Zolfaghari; Firoozeh Ahmadi; Fateme Hasani; Nima Narimani (International Journal of Reproductive BioMedicine)
Background: Endometrioma, a common manifestation of endometriosis, often indicates the severity of the disease. In vitro fertilization and embryo transfer (ET) are key therapeutic strategies for infertility associated with endometriosis. However, the optimal type of ET (frozen or fresh) and its impact on pregnancy success rates remain debated, with limited studies available.